Treatment of emphysema using bronchoscopic lung volume reduction coil technology: an update on efficacy and safety - Jorine E. Hartman; Karin Klooster; Nick H.T. Ten Hacken; Dirk-Jan Slebos (Therapeutic Advances in Respiratory Disease, 2015)
In the last decade several promising bronchoscopic lung volume reduction (BLVR) treatments were developed and investigated. One of these treatments is BLVR treatment with coils. The advantage of this specific treatment is that it works independently of collateral flow, and also shows promise for patients with a more homogeneous emphysema disease distribution. Seven years ago, the very first patients were treated with BLVR coil treatment and currently large randomized, controlled trials are underway. The aim of this article is to review the available literature and provide an update on the current knowledge on the efficacy and safety of BLVR treatment with coils.